Irrigation agriculture and groundwater. The case of Miralbueno aquifer (Spain) - Causape Valenzuela, J.
(Es, En)
Ilus., 20 ref.
Keywords: SISTEMAS DE RIEGO; AGRICULTURA DE REGADIO; AGUAS SUBTERRANEAS; EFICACIA; RIEGO; ESPAÑA